Pengaruh Kegiatan Funcooking Terhadap Kreativitas Anak Usia 5-6 - Pratiwi, Nanda; Mastuinda; Eriani, Eva; Muthie, Imam (Diklus: Jurnal Pendidikan Luar Sekolah, 2025)
The current development of learning requires teachers to implement more creative and varied instructional approaches. However, in reality, many learning activities are still applied in a monotonous and unvaried manner, which can indirectly hinder children's creativity. This study aims to examine the effect of funcooking activities on the creativity of children aged 5–6 years. The research employed a quantitative approach with an experimental method, using two learning groups: an experimental group and a control group. Data were collected through observation to assess the development of children's creativity. The study was conducted in three stages: pretest, treatment, and posttest. The experimental group received the funcooking treatment, while the control group followed conventional learning. The results showed a significant increase in children's creativity between the pretest and posttest after the treatment was given. Therefore, funcooking activities are highly suitable for implementation both in schools and at home